The biological impacts of CEBPD on urothelial carcinoma development and progression - Chan, Ti-Chun; Shiue, Yow-Ling; Li, Chien-Feng (Frontiers in Oncology, 2023)
Urothelial carcinoma (UC) which includes bladder urothelial carcinoma (UBUC) and upper tract urothelial carcinoma (UTUC) is one of the most common malignancies worldwide. Accordingly, a comprehensive understanding of the underlying mechanism governing UC development is compulsory. Aberrant CEBPD (CCAAT/enhancer-binding protein delta), a transcription factor, displays an oncogene or tumor suppressor depending on tumor type and microenvironments. However, CEBPD has been reported to possess a clear oncogenic function in UC through multiple regulation pathways. Genomic amplification of CEBPD triggered by MYC-driven genome instability is frequently examined in UC that drives CEBPD overexpression. Upregulated CEBPD transcriptionally suppresses FBXW7 to stabilize MYC protein and further induced HK2-related aerobic glycolysis that fuels cell growth. Apart from the MYC-dependent pathway, CEBPD also downregulates the level of hsa-miR-429 to enhance HK2-associated glycolysis and induce angiogenesis driven by VEGFA. Additionally, aggressive UC is attributed to the tumor metastasis regulated by CEBPD-induced MMP2 overexpression. Furthermore, elevated CEBPD induced by cisplatin (CDDP) is identified to act as a dual function to occur CDDP-induced chemotherapy resistance or drive CDDP-induced anti-tumorigenesis. Given the role of CEBPD in UC is getting clear but pending a more systemic reappraisal, this review aimed to comprehensively discuss the underlying mechanism of CEBPD in UC tumorigenesis.